O17 Transforming sexual health systems through online services. (8th June 2017) - Baraitser, Paula; Turner, Katherine; Brady, Michael; Sa, Joia de; Syred, Jonathan; Howroyd, Chris; Holdsworth, Gillian
Abstract : Introduction: Online sexual health services can transform sexual health systems through increased access and self-management. They are one element of the whole sexual health economy. Best practice facilitates appropriate movement of users between online and clinic services according to their sexual health need. Methods: Using routinely collected, anonymised service activity data, SHHAPT codes, and interviews with users/providers we studied online options for system transformation in sexual health services in two London Boroughs with high rates of sexual ill health. We focused on: Total sexually transmitted infection testing capacity; Access for new populations; Testing and treatment choices; Online contraceptive pills provision Results: Online services increase STI testing capacity, total testing in the area by 9.6% from 73, 714 (01/04/14–31/3/15) to 80, 757 (01/04/15–31/03/16). 90.8% of online users were asymptomatic with a positivity rate of 6.8%. Users move between online and clinic – 55% of online users had used a clinic within the last year and 6.8% of online users were referred to clinics. The online service engaged new populations – 19% of online users had never used a clinic before. 11, 353 treatments for chlamydia were provided across the whole system (2015/16). A pilot of online treatment and partner notification shows 95% uptake demonstrating the potential impact of an online only chlamydia management pathway. Users engage with online medical histories, self reported blood pressure and SMS based clinical conversations for contraceptive prescribing. Discussion: Online services can transform sexual health systems by increasing capacity, increasing access and by offering new treatment choices.